The importance of field research in efficient water use in Kashkadarya region - Matyakubov B.; Yakhyoev O.; Karabayev A.; Altmishev A. (BIO Web of Conferences)
The article presents long-term data on the efficient use of water in the Kashkadarya region, as well as their analytical indicators. Agricultural crops, including cotton, require a certain level of moisture in the active layer during the development phases. Natural rainfall is insufficient for optimal soil moisture in cotton cultivation. Therefore, there is a need to artificially moisten the active layer of the soil. There are many forms and methods of artificial soil moistening. At a time when water resources are scarce, the application of new water-saving irrigation technologies is of great importance. At the same time, water-saving technologies have been introduced to 1.3 million (30%) of the 4.3 million irrigated areas in the Republic of Uzbekistan. Out of this, drip irrigation is used on 475 thousand hectares, sprinkler irrigation on 49 thousand hectares, discrete irrigation on 29 thousand hectares, flexible pipe on 45 thousand hectares, film on 27 thousand hectares, and laser leveling on 674 thousand hectares. Based on this, it is stated that 22% of the total area of Kashkadarya region is being used for research on the use of water-saving irrigation technology, and as a result, up to 40% of irrigation water has been saved. According to the results of the research, it is possible to obtain a large and high-quality cotton yield by maintaining the limit field moisture capacity (MFWC) of the soil at 70-75-60 percent before irrigation from under the soil of cotton. In the conditions of experimental field soils with medium mechanical composition, the length of the sprinkler (60-250 m.), the distance between the sprinklers (1.25-1.50 m.) was used. It has been proven that irrigation water planning should be managed based on water evaporation. The average monthly amount of evaporation in Kashkadarya region was 5.16 mm, and the highest evaporation was observed in June and July, and the average annual precipitation was 111.4 mm. It was mentioned that 80 percent of the time of the year falls on the autumn-winter seasons.